Building on the successes of patient-focused drug development: a call for new policies to maintain momentum - Martin, Allison; DiBiaso, Victoria; Bozic, Mladen; May, Alexander T. (Frontiers in Medicine, 2024)
•Since its commencement as part of the Food and Drug Administration’s (FDA) Prescription Drug User Fee Act (PDUFA) V in 2012, patient-focused drug development (PFDD) has become an integral part of the drug development paradigm. •FDA encourages the development and use of Patient-Experience Data (PED) as it provides important information on the patients’ needs and perspectives and inform regulatory decision-making. •While the FDA is required to fill out a table which includes a list of various types of PED and if such data was reviewed by FDA as part of a drug application, there is still a need to understand how FDA uses PED in its regulatory decision-making. •This article examines whether new policies are needed to ensure the full potential of PFDD.